Proficiency testing scheme based on ISO/IEC 17043 in Indonesia: Strategy in complying the technical requirements for the proficiency testing providers - Fransiska Sri Herwahyu Krismastuti (Research Center for Chemistry - LIPI, 2021)
Proficiency testing (PT) is conducted by accredited providers to assure the validity of measurements conducted by laboratories. ISO/IEC 17043 is the international standard used to assess the competency of PT providers. It consists of five clauses; scope, normative references, term and definitions, technical requirements, and management requirements. Compliance with the ISO/IEC 17043 has been challenging for PT providers especially for the new PT providers tried to gain accreditation for ISO/IEC 17043. The challenges and benefits for the PT providers on implementing ISO/IEC 17043, especially the technical requirements, are discussed with particular emphasis on the homogeneity and stability testing, statistical design, packaging and distribution of PT samples. This discussion is expected giving enlightenment for the new PT providers in complying with the ISO/IEC 17043.